(untitled) - AYU CANDRAWATI, SEPTIANI (LATERNE, 2014)
Lesson method is important substance in learn process, even if that is not the only factor to fixed the success of students study. An approach used to reach the learn purpose, meanwhile the influence of applying the lesson method are there students skills development during delivery processing of learn material. It is interested to use that strategy at reading section of Germany language lesson. The porpose of this research is to describe applying guided discovery strategy at reading section of Germany language lesson. This research use quantitative method. There is decrease on students lesson result from the first to the second meeting as followes; (72,8) (56,3) (73,7) and (75,9). Decrease those lesson result caused by students difficulties for using Germany language structure,specially morphology and syntax. Because of those, the answer of problem formulation this research, that guided discovery strategy can notused as alternative strategy in reading section of Germany language lesson to improve the students skills. Keywords: guided discovery strategy, reading section